2010
DOI: 10.1128/aem.01767-10
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Biomineralization of Fluorescent Calcite by the Thermophilic Bacterium Geobacillus thermoglucosidasius

Abstract: The thermophilic Geobacillus bacterium catalyzed the formation of 100-m hexagonal crystals at 60°C in a hydrogel containing sodium acetate, calcium chloride, and magnesium sulfate. Under fluorescence microscopy, crystals fluoresced upon excitation at 365 ؎ 5, 480 ؎ 20, or 545 ؎ 15 nm. X-ray diffraction indicated that the crystals were magnesium-calcite in calcite-type calcium carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…The authors observed similar effects in the case of calcium carbonate precipitation on concrete mediated by the same ureolytic bacteria (15). Although they provided no explanation for the change in the morphology (and phase) of bacterial precipitates, it could be argued that acetate ions, acting as an additional carbonyl carbon source (93), can lead to higher bacterial activity, EPS production, and supersaturation. High supersaturation and abundant organics may, in turn, kinetically favor vaterite precipitation, as discussed above.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The authors observed similar effects in the case of calcium carbonate precipitation on concrete mediated by the same ureolytic bacteria (15). Although they provided no explanation for the change in the morphology (and phase) of bacterial precipitates, it could be argued that acetate ions, acting as an additional carbonyl carbon source (93), can lead to higher bacterial activity, EPS production, and supersaturation. High supersaturation and abundant organics may, in turn, kinetically favor vaterite precipitation, as discussed above.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that bacterial attachment to solid substrates has a significant impact on bacterial resistance to physicochemical stressors (93) and enhances bacterial metabolic activity and growth (36,52). Manini and Luna (55) reported that bacterial heterotrophic production is enhanced in calcite microcosms and is reduced in quartz microcosms by using marine bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomineralization refers to the synthesis of inorganic mineral-like materials by living organisms through the combination of chemical elements and such organisms in the same system. Bacteria can form inorganic crystals either intracellularly or extracellularly [24], generating by-products, such as the precipitation of calcium carbonate, as shown in Fig. 1.…”
Section: Materials: Pore Network In Geological Forma-tionsmentioning
confidence: 99%